2002
DOI: 10.1111/j.1749-6632.2002.tb04910.x
|View full text |Cite
|
Sign up to set email alerts
|

Theories in Early Embryology

Abstract: In current biological and philosophical literature, the use of the terms epigenesis and epigenetics has increased tremendously. As these terms are often confused, this paper aims at clarifying the distinction between them by drawing their conceptual and historical evolutions. The evolution of the term epigenesis is situated in the context of early embryological studies. Departing from Aristotle's natural philosophy, it is shown that epigenesis gained alternating attention from the 17th century onwards, as it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Realizing that all cells in an organism are derived from a single cell (the zygote) and that they share an almost identical genetic information has left open a crucial question: what is the molecular substrate accounting for the differences between cell types. At the beginning of the twentieth century, Waddington has famously proposed that lineage commitment happens akin to a falling ball bound by tracts and walls consisting of epigenetic modification (1)(2)(3)(4). Subsequent discoveries have clearly demonstrated that epigenetic changes indeed orchestrate ontogeny and that this molecular mechanism is perverted and hijacked in malignant diseases against the benefit of the organism itself (5).…”
Section: Background On Dna Methylationmentioning
confidence: 99%
“…Realizing that all cells in an organism are derived from a single cell (the zygote) and that they share an almost identical genetic information has left open a crucial question: what is the molecular substrate accounting for the differences between cell types. At the beginning of the twentieth century, Waddington has famously proposed that lineage commitment happens akin to a falling ball bound by tracts and walls consisting of epigenetic modification (1)(2)(3)(4). Subsequent discoveries have clearly demonstrated that epigenetic changes indeed orchestrate ontogeny and that this molecular mechanism is perverted and hijacked in malignant diseases against the benefit of the organism itself (5).…”
Section: Background On Dna Methylationmentioning
confidence: 99%
“…Waddington created the catchy neologism epigenetics through amalgamating Aristotelian epigenesis with modern genetics . Over the centuries, epigenesis (the classical view that biological structures and organisms come into existence and develop gradually, as a result of a succession of numerous steps and interactions from a relatively formless state to a formed one) has been contrasted with preformationism (an outlook where the individuals and their parts are seen as pre formed or pre determined) (Müller and Olsson , 114–23; Speybroeck, Waele, and Van de Vijver , 7–34). This antagonism has mutated and surged under different insignia—not necessarily confined to the field of embryology: for instance, ‘soft’ inheritance and environmental plasticity versus ‘hard’ inheritance and genetic determinism or—more popularly—biology versus upbringing and experience.…”
Section: Epigenetics In Societymentioning
confidence: 99%
“…Morphogenesis, originating from the Greek words morphe/shape and genesis/formation, is a fascinating biological process that has attracted human eyes since ancient times (Theophrastus, 1916). Several model systems have been used to study morphogenesis, from the first examination of chicken embryos by Aristotle (Speybroeck et al, 2006;Munjal et al, 2015;Petit et al, 2017;Sutherland et al, 2020). Plants provide an excellent model system to investigate the shaping of an organism during the adult life cycle (Lintilhac, 2014;Pałubicki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Aristotle's philosophy shaped our thinking of the term 'form' as fulfilling the full potential and destiny of oneself (Speybroeck et al, 2006). Leaves are vital photosynthetic, lateral organs produced by the plant throughout its life cycle.…”
Section: Introductionmentioning
confidence: 99%